Treatment of sarcopenia and glucose intolerance through mitochondrial activation by 5-aminolevulinic acid - Chikako Fujii (Nature Portfolio, 2017)
Abstract Recently, sarcopenia has attracted attention as therapeutic target because it constitutes a risk factor for metabolic and cardiovascular diseases. We focused 5-aminolevulinic acid (ALA) which act as electron carriers in the mitochondrial electron transport system. The mice that received ALA for 8 weeks gained muscle strength and endurance, and exhibited increased muscle mass and mitochondrial amount. Administration of ALA to sarcopenia mice aged 100 weeks and chronic kidney disease (CKD) model mice also increased muscle mass and improved physical performance. Metabolome analysis revealed increased branched-chain amino acids (BCAAs) levels in the skeletal muscle of ALA-treated mice. Quantitative PCR analysis revealed decreased expression levels in branched-chain amino acid transaminases (BCATs) that degrade BCAAs and other muscle-degrading factors, and increased levels of mitochondria-activating factors. We also studied in cultured myocytes and obtained compatible results. ALA-treated mice tended to increase body weight, but reduced blood glucose level. These suggested that ALA treatment not only activated muscle mitochondria but also enhanced muscle mass through an increase in BCAAs contents, as to improve muscle strength, endurance and glucose tolerance in mice. In these ways, muscle mitochondrial activation with ALA is suggested to be useful for the treatment of sarcopenia and glucose intolerance.